2020
DOI: 10.1096/fj.201901819rr
|View full text |Cite
|
Sign up to set email alerts
|

Role of dendritic cell‐mediated immune response in oral homeostasis: A new mechanism of osteonecrosis of the jaw

Abstract: Dendritic cells are an important link between innate and adaptive immune response. The role of dendritic cells in bone homeostasis, however, is not understood.Osteoporosis medications that inhibit osteoclasts have been associated with osteonecrosis, a condition limited to the jawbone, thus called medication-related osteonecrosis of the jaw. We propose that disruption of the local immune response renders the oral microenvironment conducive to osteonecrosis. We tested whether zoledronate (Zol) treatment impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Generation of BMDCs was performed as previously described ( Elashiry et al., 2020 ; Elsayed et al., 2020 ). Briefly, bone marrow was isolated from femurs and tibiae of young (2 months) and old (22-24 months) C57B6 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Generation of BMDCs was performed as previously described ( Elashiry et al., 2020 ; Elsayed et al., 2020 ). Briefly, bone marrow was isolated from femurs and tibiae of young (2 months) and old (22-24 months) C57B6 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Antigen presentation. To study the antigen-presenting ability of E. faecalis-induced DCs for CD4 ϩ T cells, the spleens of OT-II transgenic mice were dissected, and T cells were isolated to 95% purity using negative selection with a mouse T cell enrichment kit (MagniSort; Thermo fisher Scientific) and then stained with CFSE as previously described (47). The E. faecalis-induced DCs and control DCs were incubated with OVA peptide (O1641; MilliporeSigma).…”
Section: Methodsmentioning
confidence: 99%
“…Orsini et al demonstrated that BPs modulate the maturation of DCs but have no effect on the differentiation of DCs ( 42 ). Recently, it was shown that zoledronate (nitrogen-containing BPs) treatment decreased the number of infiltrated DCs in soft tissues and impaired the phagocytosis of DCs, thereby leading to an increased bacterial load and the occurrence of MRONJ ( 43 ). There are few reports on the underlying mechanism of BPs-mediated dysfunction of DCs, however, the immune suppression and inflammation in the oral cavity caused by dysfunctional DCs may provide new insights into the pathogenesis of MRONJ.…”
Section: The Mucosal Immune Response and Mronjmentioning
confidence: 99%
“…Additionally, decades of reports have identified that immune cells participate and mediate skeletal homeostasis by releasing multiple types of cytokines ( 94 ). Elsayed et al found that DCs play a significant role in post-extraction homeostasis in alveolar bone ( 43 ). Osteal macrophages were reported to locate adjacent to osteoblasts and regulate bone formation, playing diverse roles in skeletal homeostasis ( 95 ).…”
Section: The Osteo Immune Response and Mronjmentioning
confidence: 99%